Pencegahan Penularan Virus Corona di Masjid Agung Baitul Mukminin Kabupaten Jombang - Dana Fauziah Muslimah; Ahmad Suyuthi (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
The purpose of this study was to see how successful the implementation and the resulting impact on the Jombang Regency regent's regulations were in preventing the transmission of the corona virus which was located at the Baitul Mukminin Great Mosque of Jombang Regency. The method used is descriptive qualitative research method with the type of qualitative research-case study. Data collection techniques using interviews, observation and documentation. This study uses the theory of implementation model by Edwards George III and impact thinking by Thomas R. Dyee. In this research produce. The findings of this study are: first, during the implementation of the health protocol, there was a change in behavior for both the takmir of the mosque and the congregation of the mosque. The difference is that at the beginning of the pandemic, they were very strict in implementing the protocol, but over time during the new normal, the level of awareness has decreased. This happened because the mosque was inconsistent in implementing protocol discipline and the congregations who were still there were negligent of the health protocol. In addition, the monitoring carried out by the government and the mosque was not optimal. Second, in every policy that is implemented, there will always be an influence or impact, both positive and negative impacts, including in the health protocol policy